Eco-Nanozymology: A Catalytic Paradigm Integrating Energy, Environment, and Ecology - Shang, Limin; Zhang, Ziqi; Lin, Hongyu; Wang, Zichang; Chen, Dehong; Zhu, Zhiling (Nano-Micro Letters, 2026)
Eco-nanozymology, as an emerging interdisciplinary field, integrates nanotechnology with principles of enzymology to offer innovative strategies for energy conversion and environmental remediation. In contrast with conventional enzymology, eco-nanozymology enhances catalytic efficiency through the precise regulation of interfacial microstructures, electronic distributions, active site configurations, multienzyme cascade catalysis, and functionalized carrier engineering. By harnessing and amplifying natural ecological processes, eco-nanozymology enables effective modulation of energy flow and material cycling within ecosystems. This review focuses on recent advances in the application of eco-nanozymology across energy-related domains, including nitrogen fixation, carbon fixation, methane oxidation, hydrogen production, and energy conversion devices. It further provides an in-depth analysis of the recent progress in the efficient degradation of environmental pollutants and resource-oriented valorization of low-value biomass, such as lignin, agricultural residues, livestock manure, and microplastics. These studies highlight the pivotal role of eco-nanozymology in enhancing the efficiency of environmental management, accelerating the development of green energy technologies, and advancing carbon neutrality goals. The continued development of eco-nanozymology is expected to open new horizons for the deepening and expansion of nanozyme applications, offering green, environmentally friendly, and sustainable technological pathways to address global energy and environmental challenges. Highlights: 1 Eco-nanozymology is proposed as an ecosystem-oriented framework integrating cross-scale energy and matter cycling. 2 Ecological nanozymes demonstrate significant advances in energy conversion and environmental remediation. 3 Eco-nanozymes enable improved remediation efficiency, green energy technologies, and carbon neutrality.